Patenting activity of Canadian-resident businesses - Chahreddine Abbes; John Baldwin; Danny Leung (Economic and Social Reports)
This article presents some initial findings from a new longitudinal database created from administrative data sources to study patenting in Canada. The study of patenting is important as patenting is a measure of innovative activity and has been linked to positive economic outcomes for firms.